This I Believe - Wilcox, Walter F. (Tufts Archival Research Center, 2006)
Walter Wilcox describes his belief that the world has steadily gotten better during his lifetime, and his belief that individuals must create order out of the personal chaos in which they find themselves, with truth and freedom as necessary components of this task.